Learning Outcome Improvement Of The Students From Sma Using Multimedia - Yusuf, Yusnidar (El Banar : Jurnal Pendidikan dan Pengajaran, 2021)
This research aims to increase the ability of students to understand and improve the learning outcome of chemical analysis in chemistry and also to improve the ability of teachers to deliver the subject. This research was conducted at SMA Angkasa Halim Perdana Kusuma di Jakarta. This research is a classroom action research which was done in 2 cycles for as long as 5 months by using two observers in the school. This is an ongoing research which is at the phase of data collection. The expected hypotheses are after watching the video or interactive software about chemical analysis, students will understand the material which is shown by happy attitude and test result improvement.